Dermal Substitutes Support the Growth of Human Skin-Derived Mesenchymal Stromal Cells: Potential Tool for Skin Regeneration - Jeremias, Talita da Silva (Public Library of Science, 2014)
New strategies for skin regeneration are needed in order to provide effective treatment for cutaneous wounds and disease. Mesenchymal stem cells (MSCs) are an attractive source of cells for tissue engineering because of their prolonged self-renewal capacity, multipotentiality, and ability to release active molecules important for tissue repair. In this paper, we show that human skin-derived mesenchymal stromal cells (SD-MSCs) display similar characteristics to the multipotent MSCs. We also evaluate their growth in a three-dimensional (3D) culture system with dermal substitutes (Integra and Pelnac). When cultured in monolayers, SD-MSCs expressed mesenchymal markers, such as CD105, Fibronectin, and α-SMA; and neural markers, such as Nestin and βIII-Tubulin; at transcriptional and/or protein level. Integra and Pelnac equally supported the adhesion, spread and growth of human SD-MSCs in 3D culture, maintaining the MSC characteristics and the expression of multilineage markers. Therefore, dermal substitutes support the growth of mesenchymal stromal cells from human skin, promising an effective tool for tissue engineering and regenerative technology.